Cell Viability in Arthroscopic Versus Open Autologous Chondrocyte Implantation. (January 2017) - Biant, Leela C.; Simons, Michiel; Gillespie, Trudi; McNicholas, Michael J.
Background: Autologous chondrocyte implantation (ACI) is an effective method of repair of articular cartilage defects. It is a 2-stage operation, with the second stage most commonly performed via mini-arthrotomy. Arthroscopic ACI is gaining popularity, as it is less invasive and may accelerate early rehabilitation. However, handling and manipulation of the implant have been shown to cause chondrocyte cell death. Purpose: To assess the number and viability of cells delivered via an open versus arthroscopic approach in ACI surgery. Study Design: Controlled laboratory study. Methods: Sixteen ACI surgeries were performed on young cadaveric knees by 2 experienced surgeons: 8 via mini-arthrotomy and 8 arthroscopically. Live and dead cells were stained and counted on implants after surgery. The cell number and viability were assessed using confocal laser scanning microscopy. Surgery was timed from knife to skin until the end of cycling the knee 10 times after implantation of the cell-membrane construct. Results: On receipt of cell membranes after transportation from the laboratory, ≥92% of the cells were viable. There were significantly more remaining cells (8.47E+07 arthroscopic vs 1.41E+08 open; P < .001) and 16 times more viable cells (3.62% arthroscopic vs 37.34% open; P < .001) on the implants when they were inserted via mini-open surgery compared with the arthroscopic technique. Open surgery was of a significantly shorter duration (6 vs 32 minutes; P < .001). Conclusion: In this study, there were significantly more viable cells on the implant when ACI was performed via mini-arthrotomy compared with an arthroscopic technique. Clinical Relevance: The viability of cells delivered for ACI via an arthroscopic approach was 16 times less than via an open approach. The mini-arthrotomy approach is recommended until long-term clinical comparative data are available.